The Green Imam: An Analysis of Eco-Theology and Community-Based Climate Change Mitigation in Indonesian Mosques - Nurul Huda; Amin Zaki; Faisal Razak (Yayasan Adra Karima Hubbi, 2025)
Growing ecological degradation and rising climate vulnerabilities in Indonesia have prompted renewed interest in faith-based environmental engagement, yet the role of mosques as community hubs for climate action remains insufficiently defined. Previous studies often assume that religious leaders automatically possess ecological authority, overlooking the varied interpretations of eco-theology within local Islamic practices. This study investigates how the figure of the Green Imam—a religious leader advocating environmental ethics—can shape community-based climate change mitigation in Indonesian mosques. The research aims to analyze the theological foundations of Islamic eco-ethics, examine the agency of imams in mobilizing environmental awareness, and evaluate community responses to mosque-based climate initiatives. A qualitative design was employed, combining textual analysis of eco-theological literature, semi-structured interviews with imams from diverse regions, and case studies of mosque-led environmental programs such as waste management, tree planting, and sustainable water use. Findings indicate that eco-theology provides a compelling moral narrative that strengthens local climate action, but its effectiveness depends on the imam’s interpretive framing, leadership style, and the socio-cultural character of the congregation. Mosques implementing structured environmental programs demonstrated higher levels of community participation and stronger behavioral shifts compared to those relying solely on sermons. However, uneven ecological literacy among imams and limited institutional support remain persistent challenges. The study concludes that the Green Imam model can serve as a catalyst for climate mitigation when supported by coherent theological grounding, community empowerment strategies, and collaborative networks with governmental and civil-society actors. Strengthening eco-theological literacy and institutionalizing environmental programs in mosques are essential for long-term sustainability.